NIGERIAN TELEVISION DRAMA SERIES AND AUDIENCE REACTIONS: A SEISMOLOGY EVALUATION - Stanislaus Iyorza; Patience Abu (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2020)
The objective of this study is to find answers to evaluate reactions of the audience to the Nigerian television drama series in Nigeria, giving attention to how the programmes are making waves and the extent to which the audience has invested their knowledge, time and interest in them. Seismology is the study of effects or waves created by a dramatic piece, the entire theatrical event or radio or television programme.  This discourse assumes that the Nigerian television drama series may not be evoking the desired reactions from their audience. The problem of this study is the uncertainty surrounding the impact or waves made by the Nigerian television drama series on their audience. To achieve the objectives of this study adopted quantitative and qualitative research methods to elicit audience reaction. The study employed the survey method using questionnaire and online interview designs to elicit responses on audience responses to Nigerian television drama series. Findings revealed that more than 80% of Nigerians watch at least one or more Nigerian television drama series out of interest. Audience reactions to the programmes are in form their expressions of knowledge about the drama series in terms of best actors, producers and television drama series in Nigeria. The audience also reacted that the Nigerian television drama series is more entertaining than educational and informational, even though some combine all those qualities. The audience also agreed that the Nigerian television drama series reflect life in Nigeria by promoting good morals and criticizing anti-social behaviours like raping, drug abuse and kidnaping. The paper recommends multinational companies' continuous sponsorship of television drama series that is targeted at making the Nigerian society a better place.